2015
DOI: 10.1016/j.fsigss.2015.09.198
|View full text |Cite
|
Sign up to set email alerts
|

Finding DNA: Using fluorescent in situ detection

Abstract: It is known that DNA can be deposited onto a surface by touch yet few means have been developed for its in situ detection. Collecting touch-DNA samples can be difficult as likely locations rather than the DNA is targeted leading to many samples that are submitted to a forensic laboratory containing little or no DNA. A range of dyes are available that bind to DNA at high specificity for application within the laboratory and here we report on the use of these dyes to detect latent DNA on various substrates and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Hence, we selected Diamond Dye as a touch DNA visualization reagent. Background fluorescence mentioned in a previous study [2] due to bacterial DNA was also seen in this study.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, we selected Diamond Dye as a touch DNA visualization reagent. Background fluorescence mentioned in a previous study [2] due to bacterial DNA was also seen in this study.…”
Section: Methodssupporting
confidence: 88%
“…Touch DNA from bomb assemblers usually yields low success rate due to the inability to locate the areas where DNA has been left [1]. Previous studies showed that touch DNA and other biological fluids could be stained with a fluorescent dye but STR typing was unsuccessful because the dyes interrupt DNA extraction and other processes [2,3]. In this study, we therefore investigated the efficiency of three fluorescent dyes to locate touch DNA on the IED substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This may be supported by published observations of more DNA deposited by individuals with drier hands [42] and with active skin diseases known to elevate keratinocyte turnover [128]. Nucleic acid staining of touched items and dead skin has shown clustered fluorescence distinct from a cellular structure which could be diffuse intracellular DNA [129]. Reported rabbit polyclonal anti-ssDNA antibody staining in the outermost skin tissue has revealed a few nuclei-like objects in the cornified layers of cells, suggesting either that these cells are not as entirely devoid of DNA as was previously thought or that compromised cells have left residual nuclei.…”
Section: Fragmented or Degraded Cells Including Free Nucleisupporting
confidence: 53%
“…Diamond ™ Nucleic Acid Dye (DD) (Promega, Madison, WI, USA) has recently been reported to stain DNA in samples such as hair roots and shafts [1,2], saliva [3,4], fingermarks [5] and other forensically relevant items [6]. The DD molecule is an external groove-binder that is able to bind to the backbone of DNA effectively, but it does not bind effectively to RNA and prokaryote supercoiled DNA [1,7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%